Sosialisasi Pengelolaan Keuangan Rumah Tangga Pada Karyawan New Topsy Salon Plaza Ambarrukmo - Gabriella Julianika Erline; Hasim As’ari (Pusat Riset dan Inovasi Nasional, 2023)
Financial planning and management for employees of New Topsy Salon Plaza Ambarrukmo Yogyakarta hasn’t been done optimally. Some employees are unable to pay debts on time and unable to pay mandatory contributions because of various reasons. The purpose of this community service activity is to increase knowledge & skills in financial planning & management, especially for employees at New Topsy Salon Plaza Ambarrukmo Yogyakarta. This community service activity at New Topsy Salon Plaza Ambarrukmo, Yogyakarta was carried out on April 05, 2023. The methods used in community service activities include counseling, discussion, questions and answers. The results, shows that community service activities at New Topsy Salon Plaza Ambarrukmo, Yogyakarta succeeded in providing education about ideal financial planning to employees, including housewives and employees who aren’t married. Participants were able to understand the importance of planning finances systematically and managing expenses, income, and investments to achieve short-term and long-term financial goals.